Changes in glutathione and xanthophyll cycle pigments in the high light-stressed lichens Umbilicaria antarctica and Lasallia pustulata - Vráblíková, Hana; Barták, Milos; Wonisch, Astrid (Journal of photochemistry and photobiology. B, Biology, 2005)
Hydrated thalli of two lichen species--Umbilicaria antarctica and Lasallia pustulata--were exposed to high light (1800 micromol m-2s-1) for 30 min. High light exposure led to a decrease of total glutathione in both species, while de-epoxidation state of xanthophyll cycle pigments and non-photochemical quenching increased. In the subsequent recovery, the values of de-epoxidation state of xanthophyll cycle pigments decreased towards initial values. Glutathione (GSH) was resynthetised slowly. In conclusion, zeaxanthin-related protection is probably more involved than GSH-related protection in short-term response to high light stress in U. antarctica and L. pustulata. Faster recovery from photoinhibition in L. pustulata than U. antarctica is mainly due to faster conversion of zeaxanthin to violaxanthin and larger GSH pool of former species.
Keywords: lišejníky; xanthofyly; Light; Xanthophylls; světlo; glutathion; Glutathione; Lichens